2013
DOI: 10.1007/s00464-013-3306-8
|View full text |Cite
|
Sign up to set email alerts
|

The end of robot-assisted laparoscopy? A critical appraisal of scientific evidence on the use of robot-assisted laparoscopic surgery

Abstract: In an era of worldwide economic crisis, it is about time to start a critical discussion as to whether we should drastically limit, or even abandon, the use of robot-assisted laparoscopic surgery and focus on more cost-effective strategies of healthcare improvement. We suggest the use of robotics should be limited to well-powered, randomized clinical trials in a limited field of research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 124 publications
0
18
0
Order By: Relevance
“…The added clinical benefits of RARP compared with other treatment options for localised prostate cancer are 'controversial' as a result of 'considerable uncertainty' surrounding the clinical research results and their meaning Novara et al, 2012;Heemskerk et al, 2014;Makarov et al, 2011). The recently-updated Dutch national guidelines on prostate cancer reported a lack of randomised studies comparing surgical and non-surgical treatment modalities (IKNL, 2013).…”
Section: The Case Study Of Da Vinci Robotic Surgerymentioning
confidence: 97%
See 1 more Smart Citation
“…The added clinical benefits of RARP compared with other treatment options for localised prostate cancer are 'controversial' as a result of 'considerable uncertainty' surrounding the clinical research results and their meaning Novara et al, 2012;Heemskerk et al, 2014;Makarov et al, 2011). The recently-updated Dutch national guidelines on prostate cancer reported a lack of randomised studies comparing surgical and non-surgical treatment modalities (IKNL, 2013).…”
Section: The Case Study Of Da Vinci Robotic Surgerymentioning
confidence: 97%
“…Many respondents recognised it and described it literally as a "pressure" (as opposed to a choice). A remarkable fear of missing out ('use it or loose it') among prospective users d particularly among the Dutch medical society (Heemskerk et al, 2014) d fuelled this process. There was also a feeling of retrospective regret for patients who had undergone ORP in the past.…”
Section: Entrepreneurship-related Affordancesmentioning
confidence: 99%
“…Pediatric surgery is described as an ''orphan'' field for commercial scale innovation due to unappealingly small gross market capacity for which to seek profit through purposefully designed products [13]. Even amongst some adult specialties for which the technology is size appropriate, there has been a recent movement of diminished enthusiasm and even dissonance [12,[14][15][16]. One might interpret this disposition to be consistent with a post-peak phase of the Hype Cycle curve (Fig.…”
Section: Dismissmentioning
confidence: 80%
“…One study showed that well-trained laparoscopic surgeons may not really benefit from 3D robot systems if 3D laparoscopy is available 8. Another paper even pointed out that it was about time to start a critical discussion as to whether we should drastically limit, or even abandon the use of robot-assisted laparoscopic surgery and focus on more cost-effective strategies of healthcare improvement in an era of worldwide economic crisis 9. The comparison of robotic and 3D laparoscopic surgery is still needed.…”
Section: Introductionmentioning
confidence: 99%